Repeatability and Feasibility of Pressure Algometry for Quantifying Mechanical Nociceptive Threshold in the Thoracic Region of Calves - Williams, Helen J.; Duncan, Jennifer S.; Grove-White, Dai H.; Mahen, Philippa J.; Gillespie, Amy V. (Frontiers in Veterinary Science, 2020)
Pressure algometry is used as a pain assessment tool which determines the mechanical nociceptive threshold (MNT) pressure needed to produce a behavioural response of pain in humans and animals. If reliable this may be a useful tool for indicating thoracic pain in calves. This study measures the repeatability and feasibility of pressure algometry using a handheld digital pressure algometer (PRODPlus, Top Cat metrology) using three serial measurements applied to six sites on the thoraces of 35 healthy calves by two different operators. The range of MNTs recorded in healthy calves was 1.2 Newtons to 25 Newtons (median=10.1 IQR=7.1-14.0). A multivariable mixed effects model identified that the MNT’s recorded were influenced by Operator, Site and Calf. Intra and inter-operator reliability were measured by intra-class correlation coefficients (ICCs). Based on average ICCs, intra-operator reliability at two sites was good; one site overlying the ventral aspect of the 6th intercostal space (ICC= 0.79 95% CI (0.63-0.89)) and the other overlying the dorsal aspect of the 9th intercostal space (ICC=0.75 95% CI (0.56-0.87)). Average ICCs for three other measurement sites were moderate or poor, and one site proved unfeasible. For inter-operator agreement average ICCs showed that agreement was also good at the same 6th and 9th intercostal space, (ICCs=0.77 95% CI (0.35-0.90) and 0.77 95% CI (0.54-0.88) respectively), agreement was moderate for the remainder of the sites. This study identifies two sites that are potentially useful for monitoring of thoracic sensitivity as an indicator of pain in calves using pressure algometry using the average of three measurements and identifies sources of variability to be considered when applying the tool for clinical or research purposes.